2001
DOI: 10.1046/j.0953-816x.2001.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced inactivation and acceleration of activation of the sodium channel associated with epilepsy in man

Abstract: Generalized epilepsy with febrile seizures-plus (GEFS+) is a benign Mendelian syndrome characterized by childhood-onset febrile and afebrile seizures. Three point mutations within two voltage-gated sodium channel genes have been identified so far: in GEFS+ type 1 a mutation in the beta1-subunit gene SCN1B, and in GEFS+ type 2 two mutations within the neuronal alpha-subunit gene SCN1A. Functional expression of the SCN1B and one of the SCN1A mutations revealed defects in fast channel inactivation which are in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 32 publications
1
30
1
1
Order By: Relevance
“…Various functional effects of the GEFSϩ mutations in SCN1A have been suggested (Alekov et al, 2001;Spampanato et al, 2001;Lossin et al, 2002Lossin et al, , 2003. For the SCN1B mutation, co expression of the ␤1 subunit harboring the GEFSϩ mutation with the ␣ subunit showed slowed inactivation, suggesting an increment of Na ϩ currents in patients (Wallace et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Various functional effects of the GEFSϩ mutations in SCN1A have been suggested (Alekov et al, 2001;Spampanato et al, 2001;Lossin et al, 2002Lossin et al, , 2003. For the SCN1B mutation, co expression of the ␤1 subunit harboring the GEFSϩ mutation with the ␣ subunit showed slowed inactivation, suggesting an increment of Na ϩ currents in patients (Wallace et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…To correlate clinical phenotypes with the underlying sodium channel disorder, we and others have characterized the biophysical properties of various mutant voltage-gated sodium channels associated with epilepsy (18)(19)(20)(29)(30)(31)(32)(33). Early findings have suggested that in some cases of GEFSϩ, SCN1A mutations promote a gain of function, whereas mutations associated with SMEI disable channel function.…”
Section: Discussionmentioning
confidence: 99%
“…Alekov et al introduced R1648H into the SCN4A cDNA and expressed the clone in mammalian HEK tsA201 cells. In this context, they observed slowed inactivation and accelerated recovery from inactivation, leading to increased channel availability, but no persistent current (42). A second substitution at the same residue, R1648C, was identified in a patient with SMEI (47).…”
Section: Figurementioning
confidence: 99%
“…Functional effects of SCN1A missense mutations Twenty SCN1A missense mutations have been evaluated in functional assays (23,24,33,(39)(40)(41)(42)(43)(44)(45)(46). Functional analysis is complicated by the difficulty of cloning neuronal sodium channel cDNAs, which are uniquely unstable during propagation in bacterial cultures (unlike the muscle sodium channel cDNAs or the calcium and potassium channel cDNAs).…”
Section: Figurementioning
confidence: 99%